Improving Students’ Critical Thinking Skills Through Case Based Learning Oriented Textbook - Alfiandra; Yusuf, Syafruddin; Barlian, Ikbal (Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
The development of teaching materials is a manifestation of the lecturer's efforts to develop a strategy in learning that adjusts specific principles by making various adaptations to various learning theories. The development of teaching materials functions as a medium that will facilitate each student to achieve learning outcomes from the material to be studied. This study aims to develop a valid, practical, and effective textbook of Law and International Relation courses using case-based learning framework, and prove its potential impact on student's critical thinking skills. This development research used the Hannafin and Peck model which consists of three phases of activity: analysis, design and development and implementation, and evaluation and revision process. The results of the study showed that the developed textbook was valid after being reviewed by instructional design experts and material experts regarding the feasibility of content, presentation and language with the mean score 3.88 (valid category) for the material and 4.28 (very valid category) for the design. The textbook was declared practical after being tested at the one-to-one evaluation and small group evaluation stages with the mean score 55.67 (practical category). The field test on students’ critical thinking skills revealed that the mean score for pre-test was 60.4 and the mean score was increased for the post-test to 91.2 with an N-gain value of 0.78 (high category). This means the developed case-based learning oriented textbook effectively improves the student’s critical thinking skills.